Sick leave before and after arthroscopic partial meniscectomy due to traumatic meniscal tear. Issue 2 (June 2020) - Bergkvist, Dan; Dahlberg, Leif E.; Thorlund, Jonas Bloch; Neuman, Paul; Zhou, Caddie; Englund, Martin
Summary: Objective: There is limited knowledge on sick leave associated with arthroscopic partial meniscectomy (APM) due to traumatic meniscal tear and its potential gender differences. Thus, our aim was to determine gender-specific sick leave before and after APM. Method: In Skåne region, Sweden, we identified patients, aged 18–59 years diagnosed with traumatic meniscal tear without ligament injury, who had APM during 2004–2012. For each patient, we randomly sampled four age- and sex-matched reference subjects from the general population. We retrieved social insurance register data of all-cause sick leave exceeding two weeks. We analyzed the proportions and duration of sick leave with respect to days of sick leave, age, and gender. Results: The cohort comprised 604 patients (29% women), mean (SD) age 40 (11) years, and 2254 reference subjects. Thirty-nine percent of women and 27% of men had a sick leave period longer than 14 days after APM. Still, we found that a new period of sick leave longer than 14 days, initiated on the day of APM (and not before), was relatively uncommon and equally distributed (15%) between women and men. Conclusion: About one-third of the patients have more than 2 weeks of sick leave after APM for a traumatic meniscal tear and women are overrepresented in this category. Prolonged sick leave initiated on the day of APM was relatively uncommon. Other factors than surgery seem to explain the prolonged sick leave.